Topological model and analysis of the P2P BitTorrent protocol. (27th November 2012) - Zhong, Ling; Kihl, Maria; Wang, Xiaofan
In this paper, we propose a directed and weighted graph model for describing P2P networks using the BitTorrent protocol. Then, we analyse the topological properties of the model based on the complex networks theory. We find that the node strength follows a power–law distribution and that there exists a positive correlation between flow betweenness and out–strength. We also include some other findings about clustering and shortest path length of these networks in our work.